Chemical Composition and Comprehensive Antimicrobial Activity of an Ethanolic Extract of Propolis from Tunisia - Nermine Nefzi; Stefania Pagliari; Luca Campone; Wided Megdiche-Ksouri; Filippo Giarratana; Nicola Cicero; Graziella Ziino; Luca Nalbone (MDPI AG, 2023)
In the present study, the chemical composition and the in vitro antimicrobial and antibiofilm activity of an ethanolic extract of propolis (EEP) from Tunisia against different ATCC and wild bacterial strains were evaluated. In situ antimicrobial activity and sensory influence of different EEP concentrations (0.5% and 1%), also in combination with 1% vinegar, were evaluated in chilled vacuum-packed salmon tartare. Furthermore, a challenge test was performed on salmon tartare experimentally contaminated with Listeria monocytogenes and treated with the different EEP formulations. The in vitro antimicrobial and antibiofilm activity was observed only against Gram-positive bacteria, such as L. monocytogenes and S. aureus, both ATCC and wild. Results of the in situ analyses revealed significant antimicrobial activity against aerobic colonies, lactic acid bacteria, Enterobacteriaceae and Pseudomonas spp. only when the EEP was used at 1% and in combination with 1% vinegar. The 1% EEP in combination with 1% vinegar was the most effective treatment also against L. monocytogenes, although 0.5% and 1% EEP used alone also showed antilisterial effects. After 7 days of storage, the sensory influence on odor, taste and color of salmon tartare was negligible for all EEP formulations. In this background, results obtained confirmed the antimicrobial efficacy of propolis which could be proposed as a suitable biopreservative to ensure safety and improve the quality of food.